PRELIMINARY INVESTIGATION ON ANTIPYRETIC ACTIVITY OF CUSCUTA REFLEXA IN RATS - Bodhisattva Roy; Sanjib Bhattacharya (Wolters Kluwer Medknow Publications, 2010)
In present study, the antipyretic activity of aqueous and ethanol extracts fromCuscuta reflexa Roxb. (Cuscutaceae) was evaluated using Brewer's yeast inducedpyrexia in rats. Both the extracts at 200 and 400 mg/kg body weight dose significantly (p< 0.05) reduced the increased rectal temperature. The extracts started reducing theelevated rectal temperature after 3 h of treatment in a dose related manner. At the dose of400 mg/kg body weight the aqueous and ethanol extract reduced 79 % and 83.8 %respectively of the elevated rectal temperature as compared to reference drug paracetamol(96.5 %) after 6 h of treatment. It was therefore concluded that both the extracts of C.reflexa demonstrated antipyretic activity, the ethanol extract was found to be slightlypotent than the aqueous extract.